(untitled) (Conferencea, 2023)
When considering the advantages of using innovative technologies and ways of development in the system for the development of shooting training, it can be concluded that the wide use of such systems during the training of OHTM trainees allows for more effective mastering of the tactical and technical elements of a combat conflict. The main directions and development prospects of the Electron simulator were determined. The use of innovative technologies serves as the main factor in the achievement of high results of various units in the performance of their combat tasks.